MEKANISME PERTAHANAN DIRI DALAM NOVEL “ADZRA’ JAKARTA” KARYA NAJIB KAELANI (PSIKOANALISIS SIGMUND FREUD) - Azzah Tuslihun Nadiyah; Wulandari; Muhsin Riyadi (An-Nas, 2023)
This research was conducted to obtain a clear description of the events of the self-defense mechanism in the novel 'Adzra’ Jakarta by Najib Kaelani so that the results can be implied in the Study of Arabic Literature for Arabic Language and Literature students, Syekh Nurjati Islamic State University Cirebon. This study uses a qualitative descriptive method with content analysis,namely about the events of the self-defense mechanism in the novel 'Adzra’ Jakarta by Najib Kailani. Based on the results and discussion in this study, the forms of self-defense mechanisms contained in the novel Adzra'u Jakarta by Najib Kailani are Repression (5), Sublimation (3), Projection (4), Diversion (11), Rationalization (14), Reaction Formation (2), Regression (11), Aggression/Apathy (12/2), and Fantasy/Stereotype (2/1). In this study the researchers found (67) self-defense mechanisms. The implication of this research for the study of Arabic Literature is to make the novel Adzra’ Jakarta by Najib Kailani as one of thelecture materials, especially in learning Arabic Literature Studies.